Pro-apoptoticeffect of diterpenoids from Fokienia hodginsii on acute myeloid leukemia cells. Issue 22 (18th November 2021) - Hau, Dang Viet; Sa, Nguyen Hoang; Tam, Nguyen Thanh; Diep, Nguyen Thi; Hoang Anh, Nguyen Thi; Thuy Linh, Nguyen Thi; Ngoc Ni, Huynh Thi; Adorisio, Sabrina; Delfino, Domenico V.; Thuy, Trinh Thi
Abstract: Previously, we isolated four known diterpenoids, trans -communic acid (1 ), 13-oxo-15, 16-dinor-labda-8(17), 11 E -diene-19-oic acid (2 ), 3 β -hydroxytotarol (3 ), and totarolone (4 ) from Fokienia hodginsii leaves. Further study demonstrated the antiproliferative activity of all four compounds in acute myeloid leukemia (OCI-AML) cells due to impaired cell cycle progression. Interestingly, 3 β -hydroxytotarol (3 ) had very powerful bioactivity at low concentrations (5 µg/mL). Graphical Abstract: